2014
DOI: 10.1139/bcb-2014-0046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel lysyl oxidase-like 2 alternative splicing isoform, LOXL2 Δe13, in esophageal squamous cell carcinoma

Abstract: Lysyl oxidase-like 2 (LOXL2) participates in every stage of cancer progression and promotes invasion and metastasis. In this study, we identified a novel alternative splicing isoform of LOXL2, namely LOXL2 Δe13, which lacked exon 13. Deletion of exon 13 caused an open reading frame shift and produced a truncated protein. LOXL2 Δe13 was expressed ubiquitously in cell lines and tissues and was mainly localized to the cytoplasm. Although it showed impaired deamination enzymatic activity compared with full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Furthermore, a 50‐kDa band was also detected with an anti‐N‐terminus antibody (unpublished data), indicating that the 50‐kDa protein is unlikely to be a processed product of 92 kDa, but is most likely a splice variant. Indeed, a LOXL2 splice variant has been reported that skips exon 13 and splices out 24 amino acids; however, this deletion does not explain the 42‐kDa discrepancy, suggesting 50‐kDa product might be a splice variant which has not been identified and remains to be clarified.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a 50‐kDa band was also detected with an anti‐N‐terminus antibody (unpublished data), indicating that the 50‐kDa protein is unlikely to be a processed product of 92 kDa, but is most likely a splice variant. Indeed, a LOXL2 splice variant has been reported that skips exon 13 and splices out 24 amino acids; however, this deletion does not explain the 42‐kDa discrepancy, suggesting 50‐kDa product might be a splice variant which has not been identified and remains to be clarified.…”
Section: Discussionmentioning
confidence: 98%
“…17 In previous studies, it has been demonstrated that LOXL2 was associated with poor prognosis in a variety of tumors and that overexpression of LOXL2 can promote the invasion and metastatic activity of cancer cells. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data.…”
Section: Discussionmentioning
confidence: 99%
“…17,39,40 In addition, several LOXL2 splice variants have been found in esophageal squamous cell carcinoma, such as the variant lacking exon 13 and the variant with a deletion of 72 nucleotides, which contribute to tumor progression by a novel molecular mechanism distinct from canonical-type LOXL2. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data. The tumor-specific LOXL2 variant could enhance the proliferative, migratory, and invasive capacities of HPV-negative HNSCC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of oesophageal cancer cell lines have been described previously . KYSE150, KYSE510 and TE3 cells were maintained in RPMI‐1640 medium containing 10% foetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%